2011
DOI: 10.19030/ajbe.v4i10.6057
|View full text |Cite
|
Sign up to set email alerts
|

Ethics In The Accounting Curriculum: What Is Really Being Covered?

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…In accounting, ethics interventions are often limited to auditing courses and a pedagogy that emphasizes the code of conduct (Armitage and Poyzer 2010;Miller and Becker 2011). This is the first study that attempts to measure a change in perceptions of moral intensity as a result of a prescribed ethics intervention, incorporating the curricular content recommendations of the 2004 AACSB task force, in an Advanced Accounting course.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In accounting, ethics interventions are often limited to auditing courses and a pedagogy that emphasizes the code of conduct (Armitage and Poyzer 2010;Miller and Becker 2011). This is the first study that attempts to measure a change in perceptions of moral intensity as a result of a prescribed ethics intervention, incorporating the curricular content recommendations of the 2004 AACSB task force, in an Advanced Accounting course.…”
Section: Discussionmentioning
confidence: 99%
“…Very few US accounting programs appear to include all the material called for in the AACSB task force report. In a study of US accounting programs at 97 universities from 44 states, Miller and Becker (2011) found that most programs have very little coverage of ethical foundational topics including definitions, terminology, theory, and decision-making frameworks.…”
Section: Ethics Interventionmentioning
confidence: 99%
“…In addition to the two reasons mentioned above, the low business ethics of accounting belongs to internal reasons. According to a survey of 1200 accounting teachers from all American universities shows that the coverage rate of professional ethics courses in accounting schools is low compared with other courses, which also means that teachers attach less importance to ethics [15]. Furthermore, the company's moral culture also serves as a guide to influence the accounting business ethics.…”
Section: Accounting Fraudmentioning
confidence: 99%
“…While the level of ethics coverage through both required and elective offerings has increased during the period 2003 to 2016, it remained quite low overall (Miller and Shawver, 2018). This research is premised on improving ethics coverage in accounting education by calling for an increase of ethics education in the accounting curriculum which appears inadequately addressed (Cohen & Pant, 1989;Haas, 2005;Marzuki et al, 2017;Miller & Becker, 2011;Cohen & Pant, 1989;Loeb & Rockness, 1992).…”
Section: Extent Of Ethics Into the Accounting Curriculummentioning
confidence: 99%
“…Gray et al (1994) advocate the acquisition of moral expertise particularly when the accounting curricula is focused on the technical aspects of accounting squeezing out softer topics such as ethical behaviour. However, when discipline specific knowledge, pertinent to the accounting curriculum is considered fixed by faculty, it is unlikely to be replaced with requests to include ethics subject matter (Madison & Schmidt, 2006;Miller & Becker, 2011). In spite of this claim, proponents of ethics education continue to call for specific topics to be incorporated in the curriculum, for example, accounting manipulations and earnings management (Fiolleau & Kaplan, 2017;Fischer & Rosenzweig, 1995;Tormo-Carbó, Seguí-Mas, & Oltra, 2016).…”
Section: Curriculum Issuesmentioning
confidence: 99%